Microfluidic Device for Acoustophoresis and Dielectrophoresis Assisted Particle and Cell Transfer between Different Fluidic Media. (2015) - Abdallah, Ali; den Driesche, Sander van; Brandhoff, Lukas; Bunge, Frank; Akhtar, Mahmuda; Ebrahimifard, Reza; Clara, Stefan; Jakoby, Bernhard; Vellekoop, Michael J.
Abstract: We introduce a wide channel, micro-fluidic device for the transfer of particles and cells between different fluidic media, for example from a sample liquid to water, based on acoustophoresis (AP) as well as negative dielectrophoresis (nDEP). Rapid prototyping was used in order to determine the dimensions of the microfluidic channels and FE (finite element) simulations were performed to derive the optimal nDEP electrodes geometries. We chose to combine nDEP and AP because of the selective nature of DEP and the high throughput possibilities that the AP offers as well as the AP independence from the dielectric properties of the used media.